Pertumbuhan Ikan Bilih (Mystacoleucus padangensis Bleeker) Di perairan Sungai Aek Alian Kecamatan Balige Kabupaten Toba Samosir Sumatera Utara - Antri Poster Sianturi; Pindi Patana; Maragunung Dalimunthe (AQUACOASTMARINE, 2014)
Bilih Fish (Mystacoleucus padangensis Bleeker) is fishing commodities in the Aek Alian River District Toba Samosir. Aek Alian River recently becomes a source of fish production Bilih Fish. The presence of this fish is could help the economy of people surrounding, but activities of catching uncontroled is one of the cause of decreasing of fish population. This Study has the objectives on accessing the growth and condition factor in the Aek Alian River. Research was conducted in May to Juni 2014. by using Purposive Sampling method. Stations spreaded among river with the station I (upstream), station II (midstream), and station III (estuaries). Primary data consisted of a total length and weight in individual fish of Bilih from the field. The sample number of Bilih fish were 281 individuals which consisted of 82 male and 199 female. The growth pattern (B) of Bilih fish is negative allometrict with value of B is 2.870 male and 2.868 female. The comparison of male and female is 1:2.427. Factor condition of Bilih fish shows 0.930 male and 0.942 female which means that the body of fish is bony or less fat.Keyword : Growth, Bilih fish resources, Mystacoleucus padangensis Bleeker, Aek Alian River